Acceleration of Modular Oil and Gas Project Duration Using the Time-Cost Trade-Off Method - Iqbal, Muhammad Bob; Silvianita, Silvianita (Newinera Publisher, 2025)
Floating Production Storage and Offloading (FPSO) is an offshore floating platform designed to process and store oil Floating Production Storage and Offloading (FPSO) is a type of floating offshore platform that functions to process and store oil and gas before being distributed to consumers. A critical component of the FPSO, designed to ensure the product can be safely processed and transported, is the topside module. Currently, the Seawater Filtration Module project is facing delay challenges that impact both project cost and completion time. Using the existing case study, this research applies the Critical Path Method (CPM) to identify the critical path within the overall project schedule, as well as the Program Evaluation and Review Technique (PERT) to manage uncertainties in the completion time of critical activities. To evaluate the acceleration strategy with consideration of additional costs, the Time-Cost Trade-Off (TCTO) method is employed. The research findings indicate that the project experienced a 51-day delay from the original schedule, which targeted completion by January 31, 2024. A total of 11 activities were identified as part of the critical path contributing to the delay. To address this issue, acceleration was carried out by adding labor based on the productivity of each activity. The results show that the addition of 17 workers successfully reduced the duration of critical activities from 721 days to 670 days. Probability analysis indicated a success rate of 82.64% for the acceleration effort. Meanwhile, the cost calculation showed that the acceleration required an additional expense of Rp 30,913,709.